Solid carbon production and recovery from high temperature methane pyrolysis in bubble columns containing molten metals and molten salts. (October 2019) - Rahimi, Nazanin; Kang, Dohyung; Gelinas, John; Menon, Aditya; Gordon, Michael J.; Metiu, Horia; McFarland, Eric W.
Abstract: We study methane pyrolysis in a bubble column reactor consisting of a layer of molten NiBi alloy, and a molten salt layer floating on the metal layer. The molten metal is a pyrolysis catalyst; the molten salt layer is added for removing contaminants from the carbon product. Methane is introduced at the bottom of the reactor and the rising bubbles contain reactant and product gases together with metal vapor and flakes of solid carbon. When the bubbles rise through the molten salt layer the metal vapor condenses producing dense liquid metal droplets, which sink to the metal phase; the low-density carbon rises to the top of the salt layer. The carbon generated from the single-phase molten NiBi reactor has a different structure from that produced in the two-phase NiBi/salt reactor. The amount of metal in the carbon product is less than 5 wt %, in the two-phase reactor, compared to 83 wt % in the NiBi single-phase reactor. After subsequent purification steps one obtains solid carbon with less than 2 wt % salt contamination and no detectable metal contamination. Graphical abstract: Image 1